Barriers of Contraception Uptake in South Punjab, Pakistan - Saima Ashraf, Arooj Fatimah Khosa, Asiya Fayyaz, Fatima Bano (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the frequency of barriers to contraception uptake in women visiting outpatient department of a tertiary care hospital of South Punjab, Pakistan. Study Design: A cross-sectional study. Place and Duration: Department of Obstetrics & Gynecology, Nishtar Medical University Hospital, Multan Pakistan from September 2021 February 2022. Methodology: A total of 249 pregnant women between 18-35 years having parity >2 and willing to be part of this research were included. Basic demographic features like age, weight, parity, socioeconomic status, education status, rural/urban residential status, willingness or barriers about various contraceptive measures were recorded and analyzed by SPSS 23. Results: In a total of 249 women, mean age was 30.56±4.74 years. Residential status of 204 (81.9%) women was urban. Mean parity was 3.85±1.07. Educational level was illiterate in 125 (50.2%) women. There were 114 (45.8%) women who belonged to low socio-economic class. There were 36 (14.5%) women who were willing to use contraceptive measures while remaining 213 (85.5%) women had some sort of barriers about contraception uptake. Husband’s disapproval accounted for the most frequent barrier to contraception uptake noted in 73 (29.3%) women while ignorance, ‘against culture’, side effects and misinformation was reported by 54 (21.7%), 34 (13.7%), 34 (13.7%) and 18 (7.2%) women respectively. Educational level (p=0.008) and socio-economic class (p<0.001) were found to have significant association with barriers to contraception uptake. Conclusion: Very high proportion of women was unwilling to contraception. Husband’s disapproval for contraception was the biggest barrier behind unwillingness to contraception uptake while ignorance and ‘against culture’ were the other most frequent barriers behind unwillingness to contraception uptake. Illiteracy and low socio-economic status were found to have significant association with barriers to contraception uptake. Keywords: Culture, contraception, illiteracy, misinformation, side effects.